2022
DOI: 10.3390/ph15060757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Norelgestromin and Ethinylestradiol in Transdermal Patches on the Clinical Outcomes and Biochemical Parameters of COVID-19 Patients: A Clinical Trial Pilot Study

Abstract: The disease caused by SARS-CoV-2 is still considered a global pandemic. Transdermal patches (TP) with immunoregulators such as estrogen and progesterone compounds could be a feasible option to treat COVID-19 because of their accessibility and relative safety. The objective of the current study was to evaluate the additional treatment with norelgestromin and ethinylestradiol in TP on the clinical and biochemical evolution of COVID-19 patients. The present is a clinical-trial pilot study that included subjects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Another clinical trial illustrated the therapeutic effect of P4 treatment in the management of severely hospitalized COVID‐19 patients 91 . In addition, norelgestromin and ethinylestradiol transdermal patches could be safe and effective treatments for moderate and severe COVID‐19 patients 92 . A systematic review showed that hormone replacement therapy was positively associated with reducing COVID‐19 symptoms 93 .…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another clinical trial illustrated the therapeutic effect of P4 treatment in the management of severely hospitalized COVID‐19 patients 91 . In addition, norelgestromin and ethinylestradiol transdermal patches could be safe and effective treatments for moderate and severe COVID‐19 patients 92 . A systematic review showed that hormone replacement therapy was positively associated with reducing COVID‐19 symptoms 93 .…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%
“… 91 In addition, norelgestromin and ethinylestradiol transdermal patches could be safe and effective treatments for moderate and severe COVID‐19 patients. 92 A systematic review showed that hormone replacement therapy was positively associated with reducing COVID‐19 symptoms. 93 There is some evidence that P4 contributes to gender differences related to COVID‐19, even though the majority of studies looked at the potential role of estrogen against COVID‐19.…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%